Historical Trends in the Hepatitis C Virus Epidemics in North America and Australia. (28th August 2016) - Rodrigo, Chaturaka; Eltahla, Auda A.; Bull, Rowena A.; Grebely, Jason; Dore, Gregory J.; Applegate, Tanya; Page, Kimberly; Bruneau, Julie; Morris, Meghan D.; Cox, Andrea L.; Osburn, William; Kim, Arthur Y.; et al.
Abstract: Background.  Bayesian evolutionary analysis (coalescent analysis) based on genetic sequences has been used to describe the origins and spread of rapidly mutating RNA viruses, such as influenza, Ebola, human immunodeficiency virus (HIV), and hepatitis C virus (HCV). Methods.  Full-length subtype 1a and 3a sequences from early HCV infections from the International Collaborative of Incident HIV and Hepatitis C in Injecting Cohorts (InC3), as well as from public databases from a time window of 1977–2012, were used in a coalescent analysis with BEAST software to estimate the origin and progression of the HCV epidemics in Australia and North America. Convergent temporal trends were sought via independent epidemiological modeling. Results.  The epidemic of subtype 3a had more recent origins (around 1950) than subtype 1a (around 1920) in both continents. In both modeling approaches and in both continents, the epidemics underwent exponential growth between 1955 and 1975, which then stabilized in the late 20th century. Conclusions.  Historical events that fuelled the emergence and spread of injecting drug use, such as the advent of intravenous medical therapies and devices, and growth in the heroin trade, as well as population mixing during armed conflicts, were likely drivers for the cross-continental spread of the HCV epidemics.